Helical Nanostructures: Chirality Transfer and a Photodriven Transformation from Superhelix to Nanokebab. Issue 3 (7th December 2018) - Jiang, Hejin; Jiang, Yuqian; Han, Jianlei; Zhang, Li; Liu, Minghua
Abstract: Photosensitive cinnamic acid conjugated glutamides were designed to demonstrate photocontrolled hierarchical chirality transfer and switching in self‐assembled systems. In methanol, the cinnamic acid derivatives self‐assembled into superhelices, which could be switched into nanokebabs upon UV irradiation. These two nanostructures showed opposite helicity. The chiral nanostructures could further convey their chirality to achiral fluorescent molecules and result in the emission of circularly polarized luminescence (CPL). Remarkably, the CPL followed the helicity of the chiral nanostructure rather than the inherent molecular chirality. Photodriven dimerization of the cinnamic moiety lead to a significant change in molecular packing and subsequent switching of the helicity of the formed nanostructures. Abstract : Kebab in the lab : Cinnamic acid derivatives self‐assemble into superhelices, which can be switched into nanokebabs upon UV irradiation. These two nanostructures showed opposite helicity. The chiral nanostructures can further convey their chirality to achiral fluorescent molecules and result in the emission of circularly polarized luminescence (CPL).